Early conversion to a sirolimus-based, calcineurin-inhibitor-free immunosuppression in the SMART trial: observational results at 24 and 36 months after transplantation - Guba, Markus Otto; Pratschke, Johann; Hugo, Christian; Krämer, Bernhard; Pascher, Andreas (Transplant international, 2012)
Early conversion to a calcineurin-inhibitor (CNI)-free maintenance immunosuppression with sirolimus (SRL), mycophenolate mofetil (MMF) and steroids was associated with an improved 1-year renal function as compared with a cyclosporine (CsA)-based regimen (SMART core-study). This observational follow-up describes 132 patients followed up within the SMART study framework for 36 months. At 36 months, renal function continued to be superior in SRL-treated patients [ITT-eGFR36m: 60.88 vs. 53.72 (CsA) ml/min/1.73 m2, P = 0.031]. However, significantly more patients discontinued therapy in the SRL group 59.4% vs.42.3% (CsA). Patient [99% (SRL) vs.97% (CsA) and graft 96% (SRL) vs.94% (CsA)] survival at 36 months was excellent in both arms. There was no difference in late rejection episodes. Late infections and adverse events were similar in both arms except of a higher rate of hyperlipidemia in SRL and a higher incidence of malignancy in CsA-treated patients. In a multivariate analysis, donor age >60 years, S-creatinine at conversion >2 mg/dl, CMV naïve(-) recipients and immunosuppression with CsA were predictive of an impaired renal function at 36 months. Early conversion to a CNI-free SRL-based immunosuppression is associated with a sustained improvement of renal function up to 36 months after transplantation. Patient selection will be key to derive long-term benefit and avoid treatment failure using this mTOR-inhibitor-based immunosuppressive regimen.